Application of The Concept of Maslahah by Judges to Issuance of Marriage Dispensation Due to Pregnancy in Religious Courts - Nur Mohamad Kasim; Indra Saputra Daud (Jambura Law Review, 2022)
The purpose of the study was to determine the substance of the granting of marriage dispensation due to pregnancy and to describe the implementation factors of the provision of marriage dispensation due to pregnancy in the Religious Courts. The research method used is sociological juridical research using a qualitative approach and taking three research locations in the Gorontalo area, namely the Gorontalo Religious Court, the Suwawa Religious Court and the Limboto Religious Court. This study uses prescriptive legal analysis. The results of the study, namely, substantially the provision of marriage dispensation due to pregnancy, namely the judge's consideration regarding legal considerations governing and applying the concept of maslahah if marriage dispensation is accepted/rejected the implementation factor of granting marriage dispensation due to pregnancy is considering the fate of a child who, if born without status, is rejected if the request for a marriage dispensation is rejected.